Satisfaction of Hypertension Patients Reviewed from Dimension Assurance at Community Health Center - Nerissa Nasriza; Herbert Wau (Universitas Muhammadiyah Yogyakarta, 2019)
Patient satisfaction in health care is a reflection of the quality of service provided. Assurance service quality includes knowledge, ability, friendliness, courtesy, and trustworthiness. If Assurance is not implemented properly, it will cause problems so that it can affect patient satisfaction. The purpose of this study was to determine the relationship between the quality of Assurance services and hypertension patient satisfaction. This study was a qualitative study, with a descriptive research design. The sample in this study were 4 hypertension patients and 2 health workers with a total of 6 informants. The indepth interview results showed that there was a clear relationship between information, hospitality and thoroughness in service to the satisfaction of hypertensive patients at the Community Health Center.